Solubility of CO2 in three cellulose‐dissolving ionic liquids. Issue 7 (12th May 2020) - Pérez, Eduardo; de Pablo, Laura; Segovia, José J.; Moreau, Alejandro; Sánchez, Francisco A.; Pereda, Selva; Bermejo, María D.
Abstract: The solubility of CO2 in three cellulose‐dissolving ionic liquids (1‐ethyl‐3‐methylimidazolium diethylphosphate, [Emim][DEP], 1‐allyl‐3‐methylimidazolium chloride, [Amim][Cl], and 1‐butyl‐3‐methylimidazolium chloride, [Bmim][Cl]) at temperatures within 298 and 356 K and pressures up to 6.5 MPa was determined using a Van Ness‐type apparatus (static isochoric). It was demonstrated that this device can work in isothermal and isoplethal modes, being the latter faster and more precise. Moreover, it was possible to determine CO2 solubilities in metastable liquid [Bmim][Cl]. Experimental data were modeled using the Extended Henry's law correlation and the group contribution equation of state. New parameters for the binary interaction of CO2 with ionic liquid groups were calculated.